Automated Market Maker – Impermanent Loss in High and Low Volatility Markets - Malinovský, Daniel; Teplý, Petr, 1977-; Palán, Luděk; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2023)
This study examines impermanent loss in Automated Market Makers (AMMs) across high and low volatility markets. It validates the profitability of AMM deposits in both scenarios, despite impermanent loss challenges. Trading fees drive profits in high volatility markets, although market volatility increases potential range of net returns, which may result in loss or less than expected net returns. Low volatility markets, we observe that while impermanent loss may be less pronounced, the consistent stability allows liquidity providers to capitalize on reliable trading fees, aligning with the profitability expectations of AMM deposits. These insights offer valuable guidance for market participants allowing them to enhance their decision-making processes in investing or potential development of new products for markets with high or low volatility.
Vedoucí práce: Petr Teplý
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses